Implementation of The Provision of Wages Below the Minimum Wage Provisions in Micro Enterprises and Small Businesses - Arif Prasetiyo; Siti Hajati Hoesin (UIN Sunan Gunung Djati, 2022)
This research is based on the application of wages below the minimum wage for businesses that meet the criteria for micro and small businesses. As it is known that the provisions of the district and city minimum wages are a form of safety net for the economic life of Indonesian workers. However, often a common problem for micro and small businesses is that they cannot meet the minimum wage requirements because the economic capacity of their own businesses is different from that of large businesses. Through the Employment Creation Act, the government finally made changes to the labor cluster by providing special rules for micro and small businesses in terms of providing wages below the minimum wage. The problems that will be studied in this research are regarding the requirements to be able to provide wages below the minimum wage provisions and how to provide wages under the minimum wage provisions. The method used by the author in this study is a normative juridical research. The results of the research are an explanation of the conditions for businesses that can pay their workers' wages below the minimum wage, how to make a Collective Agreement so that they can pay wages below the minimum wage.